Special techniques of teaching vocabulary to young learners - Zubaydova Nilufar Negmatullayevna; Qayumova Shaxnoza Anvar qizi (Zien Journals, 2023)
This article discusses the importance of vocabulary, its usage, learning and teaching techniques, its role in teaching young learners. Besides that, there are some general and special teaching techniques for EFL teachers and learners which are being used nowadays widely.
Keywords: young learners; vocabulary; special words